Norwegian Banks in a Recession: Procyclical Implications of Basel II - Henrik Andersen (Norges Bank, 2009)
While the new capital adequacy framework, Basel II, aims to make the banks' capital requirements more sensitive to the underlying risk of the assets, it may also introduce an additional source of procyclicality in the banking sector. A growing share of the literature has assessed the potential cyclicality of Basel II. However, only parts of the banks' assets have been considered. In addition, the cyclicality of the capital positions is usually left out of the calculations. This paper applies the stress testing framework of Norges Bank to analyse the cyclicality of capital positions and the cyclicality of Basel II capital requirements for the entire bank portfolio of Norwegian banks. We find a substantial increase in the calculated Basel II capital requirements in a recession scenario for the Norwegian economy. We also find a negative co-movement between capital positions and Basel II capital requirements. Hence, our analysis demonstrates that Basel II may introduce an additional source of procyclicality.
hdl:11250/2497641
Keywords: E32; G21; G28; G33; 330; Basel II; procyclicality; capital positions